ESRA19-0507 Use of clavipectoral fascial plane block for clavicle fracture: two case reports. (30th August 2019) - Yoshimura, M; Morimoto, Y
Abstract : Background and aims: We report cases of two patients who presented with rib fracture and received an ultrasound-guided clavipectoral fascial plane block. This block has the same analgesic effect as the brachial plexus block but can avoid the development of phrenic nerve paralysis and upper limb motor block. Methods: The first case was a 37-year-old man who presented with clavicle fracture after falling on a snowboard. An interscalene brachial nerve block was planned. However, the patient claimed that shoulder movement was not good. Thus, clavipectoral fascial plane and superficial cervical plexus blocks were performed after the induction of general anaesthesia. 15 mL of 0.375% levobupivacaine was administered to the fascia on both the medial and lateral sides of the clavicle fracture. The second case was a 71-year-old woman with chronic obstructive pulmonary disease who presented with a clavicle fracture. Respiratory examination showed that the patient's forced expiratory volume in 1 s was <1 L. Thus, a clavipectoral fascial plane block, not interscalene brachial nerve block, was scheduled to prevent phrenic nerve paralysis. 15 mL of 0.375% levobupivacaine was administered to the fascia on both the medial and lateral sides of the clavicle fracture after the induction of general anaesthesia with superficial cervical plexus block. Results: At two cases, the patient's heart rate and blood pressure were stable. They did not present with pain, no analgesic was used postoperatively. Conclusions: This is a simple and highly safe procedure that can provide anaesthesia and prolonged analgesia for clavicle fractures.